Q1.    Let A = \begin{bmatrix} 0 &1 \\ 0 & 0 \end{bmatrix}, show that (aI + bA)^n = a^n I + na^{n-1} bA, where I is the identity matrix of order 2 and n \in N.

Answers (1)
S seema garhwal

Given : 

              A = \begin{bmatrix} 0 &1 \\ 0 & 0 \end{bmatrix}

To prove :   (aI + bA)^n = a^n I + na^{n-1} bA

For  n=1, aI + bA = a I + a^{0} bA =a I + bA

The result is true for  n=1.

Let result be true for n=k, 

                                         (aI + bA)^k = a^k I + ka^{k-1} bA

Now, we prove that the result is true for n=k+1,

                                          (aI + bA)^k^+^1 = (aI + bA)^k^(aI + bA)

                                                                      = (a^k I + ka^{k-1} bA)(aI + bA)

                                                                     =a^{k+1}I+Ka^{k}bAI+a^{k}bAI+ka^{k-1}b^{2}A^{2}

                                                                    =a^{k+1}I+(k+1)a^{k}bAI+ka^{k-1}b^{2}A^{2}

A^{2} = \begin{bmatrix} 0 &1 \\ 0 & 0 \end{bmatrix}\begin{bmatrix} 0 &1 \\ 0 & 0 \end{bmatrix}

A^{2} = \begin{bmatrix} 0 &0 \\ 0 & 0 \end{bmatrix}=0

Put the value of A^{2} in above equation,

                                         (aI + bA)^k^+^1=a^{k+1}I+(k+1)a^{k}bAI+ka^{k-1}b^{2}A^{2}

                                        (aI + bA)^k^+^1=a^{k+1}I+(k+1)a^{k}bAI+0

                                                                     =a^{k+1}I+(k+1)a^{k}bAI

Hence, the result is true for n=k+1.

Thus, we have (aI + bA)^n = a^n I + na^{n-1} bA  where A = \begin{bmatrix} 0 &1 \\ 0 & 0 \end{bmatrix},n \in N.

 

 

Exams
Articles
Questions